2021
DOI: 10.3390/cancers13225844
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular Carcinoma in Non-Alcoholic Fatty Liver Disease: From Epidemiology to Diagnostic Approach

Abstract: Non-alcoholic fatty liver disease (NAFLD) is becoming the leading cause of liver morbidity worldwide and, as such, represents the pathogenic background for the increasing incidence of hepatocellular carcinoma (HCC). The annual incidence of NAFLD-related HCC is expected to increase by 45–130% by 2030. Diabetes mellitus is the most important risk factor for HCC development in NAFLD, with the risk further increased when associated with other metabolic traits, such as obesity, arterial hypertension and dyslipidemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 141 publications
0
24
0
Order By: Relevance
“…In our study, the prevalence of cirrhotic patients was slightly higher than that expected from the literature data (about 80% [23]), but compatible with a cohort in which HCV is still the main cause [24], despite a progressive increase in NAFLD as a cause (or a contributing cause) of HCC (from 17% to about 40%). This figure reflects the prediction that NAFLD will be the leading cause of HCC over the next decade [25], but it appears to have even worsened perhaps due to social restrictions and home confinement that limited physical activity; furthermore, we may have been more sensitive to reporting NAFLD as a contributing cause: in fact, its increase is not proportional to the decrease in viral infection, but is added to them. Our work presents some limitations, mainly that it is a retrospective, with limited sample size, and single-center study, which limits the applicability of our results: a validation of our results in a multicenter setting is mandatory.…”
Section: Discussionmentioning
confidence: 67%
“…In our study, the prevalence of cirrhotic patients was slightly higher than that expected from the literature data (about 80% [23]), but compatible with a cohort in which HCV is still the main cause [24], despite a progressive increase in NAFLD as a cause (or a contributing cause) of HCC (from 17% to about 40%). This figure reflects the prediction that NAFLD will be the leading cause of HCC over the next decade [25], but it appears to have even worsened perhaps due to social restrictions and home confinement that limited physical activity; furthermore, we may have been more sensitive to reporting NAFLD as a contributing cause: in fact, its increase is not proportional to the decrease in viral infection, but is added to them. Our work presents some limitations, mainly that it is a retrospective, with limited sample size, and single-center study, which limits the applicability of our results: a validation of our results in a multicenter setting is mandatory.…”
Section: Discussionmentioning
confidence: 67%
“…Chronic hepatic diseases, such as ALD and NAFLD, are emerging as the foremost cause of liver cancer and morbidity worldwide. It has been estimated that the prevalence of NAFLD-associated HCC will drastically increase (up to 45%-130%) in a decade (Grgurevic et al, 2021). The progression of hepatic diseases largely depends on several factors, such as ROS, oxidative stress, lipotoxicity, IR and gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that (mostly type 2) diabetes mellitus is associated with an increased risk of HCC development in NAFLD patients. The hazard ratio for HCC in diabetic patients has been reported to be around 2.2–4.2[ 22 , 26 , 27 ] (Table 1 ). In a nationwide Japanese study, the annual incidence of HCC was only 0.11% in diabetes patients overall.…”
Section: Clinical Risk Factorsmentioning
confidence: 99%